Impact of Social Media on Divorce Rates in Bengkulu Province (Study at the Seluma District Religious Court) - Widya Timur; Ferawati Royani; M. Vikriawan (Fakultas Hukum Dehasen, 2020)
A review of Islamic law in divorce cases on the grounds that one of the parties is cheating on social media. This study uses an empirical juridical approach. This approach aims to understand that law is not merely a set of normative laws and regulations. This study uses an empirical juridical approach. This approach aims to understand that the law is not merely a set of statutory rules that are normative in nature, but the law is understood as the behavior of people who are symptomatic in their lives, always interact and relate to social aspects, such as; economic, social and cultural aspects.